2022
DOI: 10.2113/2022/7058797
|View full text |Cite
|
Sign up to set email alerts
|

Study on Mechanism of Rock Burst in Horizontal Section Mining of a Steeply Inclined Extra-Thick Coal Seam

Abstract: With the increase of mining depth, rock burst disasters frequently occur in steeply inclined coal seams. Firstly, this paper analyzes the rock burst of 5521-20 working face in Yaojie No. 3 coal mine and summarizes the characteristics of rock burst in horizontal section mining of steeply inclined extra-thick coal seam (SIETCS). Then, the static load distribution characteristics and the influence of dynamic load in the horizontal section mining of SIETCS are systematically studied by combining theoretical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…When coal is close to a fault structure, coal stress increases, and a rock burst is easily induced [9][10][11]. In Central and Western China, coal mining is characterized by thick roofs, large mining depths, high ground stresses, and complex structural conditions which may lead to rock burst disasters.…”
Section: Introductionmentioning
confidence: 99%
“…When coal is close to a fault structure, coal stress increases, and a rock burst is easily induced [9][10][11]. In Central and Western China, coal mining is characterized by thick roofs, large mining depths, high ground stresses, and complex structural conditions which may lead to rock burst disasters.…”
Section: Introductionmentioning
confidence: 99%
“…analyzed the temporal-spatial evolution characteristics of dynamic failure in SIETCS and identified the stress concentration areas around the roadway. Wang et al (2022) studied the stress redistribution caused by horizontal section mining in SIETCS, and found that there is high shear stress in the bottom coal under the effect of "shear-clamping". Dynamic stress plays a critical role in MSTCBs (He et al, 2012;Dou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The strength theory holds that as long as the stress on the material exceeds its strength limit, the material begins to damage. According to this principle, the early strength theory holds that stress concentration occurs around the roadway and stope [11]. The stiffness theory is derived from the test theory of the rigid testing machine, which holds that if the stiffness of the testing machine is less than the later deformation stiffness of the specimen, sudden instability failure will occur [12].…”
Section: Introductionmentioning
confidence: 99%